Adding manure and zeolite to improve soil chemical properties and increase soybean yield - Slamet Minardi; Isna Luthfa Haniati; Alif Husna Lantip Nastiti (Universitas Sebelas Maret, 2020)
Increasing domestic soybean production is an important part of the effort to reduce reliance on imports. One potential area for improvement is developing soybean crops in Alfisols. Alfisols require intensive effort due to their poor soil chemical properties. Manure and zeolite were proposed as candidate materials that could be used to improve soil chemical properties to support plant growth and increase the productivity of cultivated land. The experiment was designed to study the addition of manure and zeolite on soil chemical properties of Alfisols and soybean yield. The experimental design was arranged in a factorial completely randomized block design with two factors—three rates of zeolite (Z0 = 0 t ha-1, Z1 = 2.5 t ha-1 and Z2 = 5 t ha-1) and three manure variables (P0 = no manure, P1 = 5 t ha-1 cow manure, and P2 = 5 t ha-1 quail manure)—with three replications. The results showed that a combination of 5 t ha-1 zeolite and cow manure increased soybean yield. However, zeolite 5 t ha-1 resulted in the greatest improvement in soil chemical properties—the highest CEC, soil organic matter percentage, and pH.